2001
DOI: 10.1523/jneurosci.21-12-04451.2001
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-Induced Dependence and Sensitization Are Altered in Mice Deficient in AMPA-Type Glutamate Receptor-A Subunits

Abstract: AMPA-type glutamate receptors have been suggested to be involved in the neurobiological mechanisms of drug addiction. We have made use of two mouse lines, which both have modulated AMPA receptor responses. The first line is entirely deficient in glutamate receptor-A (GluR-A) subunits (A−/− knock-out line) and, in the second one, the Q582 residue of GluR-A subunits is replaced by an arginine residue (R/R mutants), which reduces the calcium permeability and channel conductance of the receptors containing this mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 46 publications
11
73
1
2
Order By: Relevance
“…Although the GluRA(Ϫ͞Ϫ) mice were more active than WT controls, they exhibited long-lasting sensitization in response to repeated exposure to cocaine. This result is consistent with previous work reporting that GluRA(Ϫ͞Ϫ) mice exhibit sensitization to morphine and amphetamine (41), as well as with a preliminary report in which cocaine sensitization was examined (42). These results demonstrate that changes in GluRA levels and LTP in the VTA are not necessary for the development of sensitization and that other neural adaptations within the VTA must play a critical role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the GluRA(Ϫ͞Ϫ) mice were more active than WT controls, they exhibited long-lasting sensitization in response to repeated exposure to cocaine. This result is consistent with previous work reporting that GluRA(Ϫ͞Ϫ) mice exhibit sensitization to morphine and amphetamine (41), as well as with a preliminary report in which cocaine sensitization was examined (42). These results demonstrate that changes in GluRA levels and LTP in the VTA are not necessary for the development of sensitization and that other neural adaptations within the VTA must play a critical role.…”
Section: Discussionsupporting
confidence: 92%
“…The previous study that examined sensitization to morphine or amphetamine in GluRA(Ϫ͞Ϫ) mice found that a contextdependent sensitization was still present in the mutant animals, whereas ''context-independent'' sensitization was not (41). There are several explanations for this apparent discrepancy in results.…”
Section: Discussionmentioning
confidence: 91%
“…Confirming previous data, 35,47 GluR1 KO exhibited marked locomotor hyperactivity during exposure to an OF. Genotype differences were still evident after five daily 30 min test exposure.…”
Section: Discussionsupporting
confidence: 90%
“…[24][25][26][27][28][29] Previous studies have demonstrated that GluR1 knockout mice (KO) 30 exhibit behavioral abnormalities on tests for cognition, motor function and responses to drugs of abuse. [30][31][32][33][34][35][36][37] In the present study, we sought to extend these data by assessing these mice for a variety of 'schizophrenia-related' phenotypes. In addition, given the wealth of evidence implicating dysfunction of dopamine (DA) neurotransmission in schizophrenia 2 and the major interaction between the dopamine and glutamate systems, 2,38 we evaluated regulation of extracellular striatal DA in GluR1 KO in vivo using high-speed chronoamperometry.…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking GLUA1 globally throughout their lifetime display profound impairments in spatial working memory linked to increased long-term memory for novel space (Sanderson and Bannerman, 2012;Sanderson et al, 2011). They also show mild deficits in motor coordination (Bannerman et al, 2004) and massive novelty induced hyperlocomotion (Bannerman et al, 2004;Chourbaji et al, 2008c;Vekovischeva et al, 2001). Global Gria1-knockout mice have also been shown to exhibit increased learned helplessness (Chourbaji et al, 2008c) as well as mania-and schizophrenia-related behavioral abnormalities (Barkus et al, 2012;Fitzgerald et al, 2010;Wiedholz et al, 2008).…”
Section: Behavioral Phenotypementioning
confidence: 99%